Estudo de enteroparasitoses em pacientes atendidos no Hospital Universitário Lauro Wanderley município de João Pessoa-PB - Melo, Sílvia Adelaide Linhares de (2015)
Intestinal parasites diseases are responsible for serious problems in public health, intensely related to health conditions. They generate economic and social harm to the population, reducing their quality of life in developing countries and are also responsible for high mortality rates especially where health is unassisted. This study aided to analyze the association between these infections and clinical variables, haematological and epidemiological and introduce Decision Making considered by Logistic Regression model. This is an observational, analytical, cross-sectional study on the prevalence of intestinal parasites in patients treated at the Gastroenterology clinic of University Hospital Lauro Wanderley, João Pessoa, Paraíba, under the exclusive public service of Brazil’s Unified Public Health System (SUS). The data were collected by the analysis of the records from October 2014 to May 2015. Among the 370 records analyzed, through inclusion and exclusion criteria, totaled 34. The data were organized and tabulated in a spreadsheet and later submitted, through the statistical software R version 2.15.1, to a descriptive analysis and later to an associative analysis between variables as well as the Logistic Regression. The results showed that females were more affected by parasites and the average group-age of subjects was 56 years old and in general from João Pessoa. The helminth was most prevalent when compared to protozoa, being predominantly Schistosoma mansoni. The most widely used methods for fecal examinations were Hoffman and Kato-katz. Among the results of biochemical analysis, most individuals presented levels of leukocytes out of the reference values. Through the relative risk, protective factors were observed between gastrointestinal symptoms, diabetes, hypertension, and diuretic in relation to the presence of the parasite and risk factors between the independent variables and the outcome variable have been gastrointestinal comorbidities, antiparasitic medicine and gastroprotetor.